Circular Right Upper Quadrant Mass, Not Intussusception. Issue 5 (May 2015) - Chao, Jennifer H.; Saha, Abhijeet; Kapoor, Kanika; Sharma, Shilpa; Maraynes, Megan; Gullett, John
Abstract : Abstract: Point-of-care ultrasound is fast becoming a routine diagnostic tool in the pediatric emergency department, including in resource-limited settings. We describe a case where a patient was initially diagnosed with intussusception and admitted to a hospital. While serving as a patient model for a point-of-care ultrasound course, he was found to have a liver abscess. We discuss the manner in which the ultrasound study for ileocolic intussusception is performed and potential mimickers of ileocolic intussusception.